1998
DOI: 10.1089/jir.1998.18.1025
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Bioassay for the Determination of Neutralizing Antibodies to IFNβ1b

Abstract: We have adapted the new MxA gene-induction bioassay to measure neutralizing antibodies to interferon-beta1b (IFN-beta1b, the active ingredient in Betaseron) in sera from patients treated with Betaseron. This antibody assay has been validated to quantify neutralizing titers of 1:20 and above, with a precision of +/- 0.20 in log10. We have used this MxA gene-induction antibody assay to reinvestigate serum samples from multiple sclerosis (MS) patients treated with Betaseron. The titers measured were closely compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(48 citation statements)
references
References 9 publications
1
47
0
Order By: Relevance
“…The detected neutralizing activity was not characterized further by the presence of immunoglobulin in our study. As non-IgG-mediated neutralizing activity is known to occur in very few samples [14], if none from patients treated with IFN-b-1b [18], we referred as NAb + any serum where some neutralizing activity was found. However, one cannot exclude the fact that in our low titred samples, other components from the drug manufacture may have contributed in determining the antagonizing effect to IFN-b-1b.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The detected neutralizing activity was not characterized further by the presence of immunoglobulin in our study. As non-IgG-mediated neutralizing activity is known to occur in very few samples [14], if none from patients treated with IFN-b-1b [18], we referred as NAb + any serum where some neutralizing activity was found. However, one cannot exclude the fact that in our low titred samples, other components from the drug manufacture may have contributed in determining the antagonizing effect to IFN-b-1b.…”
Section: Discussionmentioning
confidence: 99%
“…Neutralizing activity detected in our samples was not characterized further as immunoglobulin (Ig)-mediated. However, as in previous work performed using this assay, non-Ig-mediated neutralizing activity contributed in very few samples [14] for this study, we referred as NAb + any serum where some neutralizing activity was found.…”
Section: Neutralizing Antibodiesmentioning
confidence: 99%
“…Anti-IFNβ neutralizing antibody titers were measured in duplicate using the MxA protein production neutralization assay [5,16]. A serum sample with a NAb titer ≥ 20 NU/mL was considered to be positive and NAb positive status was defined by two consecutive NAbpositive titers.…”
Section: ■ Measurement Of Neutralizing Antibodiesmentioning
confidence: 99%
“…The most common assay utilises the antiviral effect of IFN β and, more recently, the ability of IFN β to induce the MxA protein [10]. The former is the current method recommended by the World Health Organisation (WHO) [11], and is based on the measurement of the virus-induced cytopathic effect -the so-called CPE assay.…”
Section: Nab Assaysmentioning
confidence: 99%